2008
DOI: 10.1002/adfm.200800313
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Alkyl‐Chain Length on Beta‐Phase Formation in Polyfluorenes

Abstract: Di‐n‐alkyl substituted polyfluorenes with alkyl chain lengths of 6, 7, 8, 9, and 10 carbon atoms (PF6, PF7, PF8, PF9, and PF10) are studied in dilute solution in MCH using optical spectroscopy. Beta‐phase is formed upon cooling in solutions (∼ 7 µg mL−1) of PF7, PF8, and PF9 only, which is observed as an equilibrium absorption peak at ∼ 437 nm and strong changes in the emission spectra. Beta‐phase is formed upon thermal cycling to low temperature in solutions (∼7 µg mL−1) of PF7, PF8, and PF9, which is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
171
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(190 citation statements)
references
References 26 publications
17
171
0
2
Order By: Relevance
“…Figure 6 shows the optical absorption spectra of PF N -MCH at 10 mg/mL with the modeled fits to the spectra including the 0-0 peak, three vibronic peaks with several multiplicities, as well as a distinctive asymmetric peak at 2.9 eV. The data are qualitatively similar to those reported earlier [32,34] but the modeling allows us to estimate the relative fractions of polymer assemblies and locally free chains. The vibronic replicas used correspond to modes with energies of 85 meV (v1), 156 meV (v2), and 199 meV (v3) which were selected from fits to the β-phase PF8 photoluminescence spectrum and which agree well with Raman spectroscopy of PF8 [44].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Figure 6 shows the optical absorption spectra of PF N -MCH at 10 mg/mL with the modeled fits to the spectra including the 0-0 peak, three vibronic peaks with several multiplicities, as well as a distinctive asymmetric peak at 2.9 eV. The data are qualitatively similar to those reported earlier [32,34] but the modeling allows us to estimate the relative fractions of polymer assemblies and locally free chains. The vibronic replicas used correspond to modes with energies of 85 meV (v1), 156 meV (v2), and 199 meV (v3) which were selected from fits to the β-phase PF8 photoluminescence spectrum and which agree well with Raman spectroscopy of PF8 [44].…”
Section: Resultssupporting
confidence: 75%
“…The v2 peak increases at the expense of the v3 peak with increasing N, thus pointing to the increasing fraction of membranes and decreasing fraction of ordered sheets. The intrinsic stiffness of polymer backbones is similar for all N, as indicated by similar room temperature spectra before annealing for dilute solutions [34]. The asymmetric peak at 2.85 eV is indicative of the amount of β phase present.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…[12] Several studies have been reported, including mixing of polyfluorenes with different emissive materials and applying them in single or multiple layers. [13,14] We also know that many polyfluorenes form there own distinct phases in films, commonly known as the beta phase, [15,16,17] thus it is a ideal component of a blend to study. Polythiophenes and their regioregular forms are another class of well-known semiconductor polymers known to show complex morphology and morphological controlled pho-2 tophysics, where side chain structure and quality of solvent/environment also plays a significant role in their photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Their widespread use has benefitted from their tunable their photonic and electronic properties, which can be tailored by various methods including addition of substituents to the main core of the molecule 12,13,14 , molecular engineering of the band gaps 15 , control of morphology to extend conjugation length 16,17 , and control of film thickness 18 . The resulting materials properties in the solid-state depend not only on the electronic properties of individual molecules but also on the density of the film, i.e.…”
Section: Introductionmentioning
confidence: 99%